2010
DOI: 10.1183/09031936.00023310
|View full text |Cite
|
Sign up to set email alerts
|

Role of NF-κB and PPAR-γ in lung inflammation induced by monocyte-derived microparticles

Abstract: Microparticles (MP) are phospholipid vesicles shed by cells upon activation or apoptosis. Monocyte-derived MP upregulate the synthesis of proinflammatory mediators by lung epithelial cells; the molecular bases of such activity are unknown. Peroxisome proliferatoractivated receptors (PPAR) have been demonstrated to be involved in the modulation of nuclear factor (NF)-kB transcriptional activity and inflammation.We investigated whether the upregulation of the synthesis of proinflammatory cytokines by human lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 30 publications
3
62
0
1
Order By: Relevance
“…Rosiglitazone inhibits leukocyte MP-mediated vascular dysfunction and decreases the release of proinflammatory proteins from isolated murine aortae (69 ). Peroxisome proliferator activated receptor treatment also reduces the ability of MPs to evoke an increase in NFB and subsequently counteracts vascular dysfunction associated with increased release of proinflammatory proteins elicited by MPs in mice (70 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rosiglitazone inhibits leukocyte MP-mediated vascular dysfunction and decreases the release of proinflammatory proteins from isolated murine aortae (69 ). Peroxisome proliferator activated receptor treatment also reduces the ability of MPs to evoke an increase in NFB and subsequently counteracts vascular dysfunction associated with increased release of proinflammatory proteins elicited by MPs in mice (70 ).…”
Section: Discussionmentioning
confidence: 99%
“…Monocyte chemotactic protein 1 has been reported to be inhibited by activation of PPARγ [12,16,17]. In the late stages of lung development, increased pulmonary and circulating MCP-1 levels have been associated with the development of PH in animal models as well as human studies [18][19][20][21].…”
mentioning
confidence: 99%
“…We investigated the mechanisms leading to increased transcription of pro-inflammatory mediators induced by HMM-derived microparticles. First, we demonstrated that HMM-derived microparticles cause the translocation of NF-κB into the nucleus [36]. We then showed that PPAR-γ agonists, such as rosiglitazone and 15-deoxy-Δ 12,14 -prostaglandin-J 2 , inhibit the phenomenon [36], in keeping with the postulated anti-inflammatory role of these molecules that have in fact been proposed as potential therapeutic targets in lung diseases [37].…”
Section: Potential Role Of Microparticles In Airway Inflammationmentioning
confidence: 62%
“…First, we demonstrated that HMM-derived microparticles cause the translocation of NF-κB into the nucleus [36]. We then showed that PPAR-γ agonists, such as rosiglitazone and 15-deoxy-Δ 12,14 -prostaglandin-J 2 , inhibit the phenomenon [36], in keeping with the postulated anti-inflammatory role of these molecules that have in fact been proposed as potential therapeutic targets in lung diseases [37]. Microparticles with a similar pro-inflammatory potential on lung epithelial cells are also generated by HMMs exposed to cigarette smoke extract [24].…”
Section: Potential Role Of Microparticles In Airway Inflammationmentioning
confidence: 99%